The influence of age on a postural balance - Ewelina Stefania Pankanin (Kazimierz Wielki University, 2018)
The physiological and correct posture of a human body is a vertical attitude. A small support surface and relatively high body height cause a small but continuous balance. Maintaining a stable posture requires efficient operation of the balance system. However, with age, the involutionary changes taking place in the body impair its functioning.